The Adequacy of Cybersecurity in Financial Institutions in Zimbabwe - Mashizha, Margaret; Kanengoni, Pestalos (Universitas Prasetiya Mulya, 2024)
A well-protected cyber environment is virtually non-existent in the technical landscape of the 21st century, exposing financial institutions to risk. To preserve the well-being and trust of the public within financial systems, the financial sector needs a stable and robust cybersecurity system. This study sought to determine the causes and sources of cybercrime, the degree to which banks are aware of cybercrime, and to assess their understanding of cybersecurity and possible solutions to cyber threats. A sample of five commercial banks in Zimbabwe was surveyed and data was analyzed using descriptive statistics. Findings revealed low awareness of cybersecurity, the absence of anti-virus protection, and a cybersecurity framework. Further, the study established that financial institutions are not providing adequate financial support and training relating to cybersecurity. The study recommends investment in cybersecurity, training, and awareness campaigns to cultivate a culture of cyber alertness.